Safety and benefits of self‐expandable metallic stents with chemotherapy for malignant gastric outlet obstruction. Issue 5 (15th February 2015) - Miyabe, Katsuyuki; Hayashi, Kazuki; Nakazawa, Takahiro; Sano, Hitoshi; Yamada, Tomonori; Takada, Hiroki; Naitoh, Itaru; Shimizu, Shuya; Kondo, Hiromu; Nishi, Yuji; Yoshida, Michihiro; Umemura, Shuichiro; et al.
<x xml:space="preserve">Abstract</x> Background and Aim The influence of chemotherapy on placement of self‐expandable metallic stents (SEMS) for malignant gastric outlet obstruction (MGOO) has not been evaluated extensively. We investigated the influence of chemotherapy on the clinical outcomes of SEMS placement for MGOO. Methods A total of 152 cancer patients with MGOO from a university hospital and affiliate hospitals were included. The patients were classified according to chemotherapy status and evaluated for palliative efficacy and safety of SEMS placement. Results Technical success rate, time to oral intake, and parameters indicating improvement of physical condition did not differ between the with‐ and without‐chemotherapy groups after stent placement. Re‐intervention and stent migration were significantly more frequent in the with‐chemotherapy group than in the without‐chemotherapy group after stent placement (re‐intervention, 32.4% vs 7.8%, P = 0.0005; stent migration, 13.5% vs 1.7%, P = 0.0097). The frequency of adverse events did not differ between the with‐ and without‐chemotherapy groups. Although chemotherapy after stent placement was an independent predictive factor for shortening the stent patency period (hazard ratio [HR], 3.10; P = 0.0264), the use of additional stents facilitated uneventful recovery and further prolonged survival time (HR, 0.60; P = 0.0132). Conclusions Various cancer patients with MGOO can undergo SEMS placement safely regardless of chemotherapy, and concurrent chemotherapy after stent placement can prolong survival time, although re‐intervention and stent migration may be increased.